Peradaban Pendidikan Islam Oleh M. Quraish Shihab - Fauzia, Riani Nur; Sari, Ayang Nirmala; Mafazah, Naili (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2020)
Education is an important tool in Indonesia. Education is one of the efforts to educate the nation's children and create intellectual minds. With a clean mind and trust in Allah, an education will be well received. Then how is the State's efforts from time to time to obtain an education for the provision of this world and the hereafter. So that the result of this writing is an understanding and how to get a good education and have a good character in the Tafsir Al-Misbah discussed by the Quraish Shihab.